Labor Market Uncertainty: Can Psychological Capital Promote Career Transition Readiness in College Students? - Amalia, Ulfa; Sa'id, Mochammad (Universitas Negeri Malang, 2024)
Uncertainty in labor market conditions is a challenge for college graduates. This challenge significantly influences the length of time needed to face a career transition, so psychological capital is an important thing to have. This research aims to determine whether psychological capital can encourage students’ readiness to face career transitions. This research uses quantitative correlational methods. The population of this research were students at two public universities in Malang City who were working on their thesis with a sample size of 105 students. Sampling was carried out using incidental techniques. The instruments used were adapted versions of The Psychological Capital Questionnaire (PCQ-24) and The Career Transitions Inventory (CTI). This research uses multiple linear regression analysis techniques. The results of this research indicate that psychological capital simultaneously influences readiness to face career transitions (Sig. equals .000; f equals 33.831). The results of the coefficient of determination (Adj. R2) show a contribution of psychological capital of 55.8 percent. The t-test results show that the hope dimension (Sig. equals .008; t equals 1.256) and the optimism dimension (Sig. equals .000; t equals 4.785) partially affect career transition readiness. Meanwhile, the self-efficacy dimension (Sig. equals .212; t equals 1.256) and the resilience dimension (Sig. equals .485; t equals .701) partially do not significantly affect career transition readiness. The effective contribution of the hope dimension is 20.39 percent, and the optimism dimension is 25.84 percent.